The prevalence of declarative and indirect yes/no Questions when children testify in criminal cases of child sexual abuse in the United States. Issue 1 (28th October 2019) - Stolzenberg, Stacia N.; Morse, Stephanie J.; Haverkate, Danielle L.; Garcia‐Johnson, Anastacia M.
Summary: The present study assessed how attorneys questioned children in cases of child sexual abuse in the United States tried between 2005 and 2015. Trial testimonies ( N = 134) of 5‐ to 17‐year‐olds ( M = 12 years old) were coded for the linguistic form of attorneys' questions and children's subsequent responses. Three fourths of all questions were closed ended. Both declarative (statement question; e.g., "And he hit you?"; 21% of questions) and indirect yes/no questions (beginning with an indirect speech act; e.g., "Do you remember X?"; 11% of questions) were common, and produced potentially problematic responses, in comparison with forced‐choice and yes/no questions. Declarative questions elicited the highest rates of unelaborative responses whereas indirect yes/no questions elicited the highest rate of nonsubstantive responses. The findings highlight the importance for researchers to better assess children's responses to declarative questions and for prosecuting attorneys to cautiously use declarative and indirect yes/no questions when questioning children.